Unleashing The Philanthropy Fund’s Potential for A Sustainable Tomorrow: A Comprehensive Overview - Fatah, Anton Abdul; Andriani, Novie; Hidayat, Guntur Nur (Journal of Infrastructure Policy and Management (JIPM), 2023)
Indonesia’s dynamic philanthropic sector is pivotal for the nation’s progress and global leadership in philanthropy. Yet, its diversity and intricate regulatory landscape present challenges in maximizing the efficiency of philanthropic funds. Our extensive review highlights the imperative to bolster regulatory frameworks, enhance tax incentives, and elevate philanthropic governance. Strengthening regulations, improving tax incentives, and refining governance structures will create a more conducive environment for impactful philanthropy, empowering governments and stakeholders to drive sustainable development. These strategic actions lay the foundation for philanthropy to assume a more influential role in steering Indonesia’s path toward sustainable growth and societal well-being. By refining these essential elements, philanthropy can become a powerful catalyst in advancing Indonesia’s journey towards sustained prosperity and societal advancement.